Exceptional capacitance enhancement of a non-conducting COF through potential-driven chemical modulation by redox electrolyte - Kushwaha, Rinku; Haldar, Sattwick; Shekhar, Pragalbh; Krishnan, Akshara; Saha, Jayeeta; Hui, Pramiti; Vinod, Chathakudath Prabhakaran; Subramaniam, Chandramouli; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2021)
Capacitors are the most practical high-storage and rapid charge-release devices. The number of ions stored per unit area and their interaction strength with the electrode dictates capacitor-performance. Microporous materials provide a high storage surface and optimal interactions. Adsorbing electron-rich and easily polarizable molecules into microporous electrodes is expected to boost Faradaic pseudo-activity. If such electrode-electrolyte interactions can be made as a potential-driven reversible process, the resulting capacitors would be adaptable and device-friendly. A composite covalent organic framework (COF)-carbon electrode with redox-active KI is combined in an H2SO4 electrolyte for the first time. This composite electrode benefits from the redox-functionality of COF and electronic conductivity of carbon, leading to superior capacitative activity. Operando spectro-electrochemical measurements reveal the existence of multiple polyiodide species, although the I-3(-) is the predominantly electroactive species adsorbing on the microporous triazine-phenol COF electrode. A systematic fabrication of the flexible solid-state devices using the COF-redox-electrolyte reveals a high areal capacitance of 270 +/- 11 mF cm(-2) and gravimetric capacitance of 57 +/- 8 F g(-1). The inclusion of KI in H2SO4 (electrolyte) yields an approximately eight-fold enhancement in solid-state gravimetric specific capacitance. The imine-COF retains 89% of its capacity even after 10 000 cycles.
Keywords: covalent organic frameworks; polyiodide; redox electrolytes; solid‐ state capacitors; Supercapacitors